Struggles over human rights in local government – the case of access to education for undocumented youth in Malmö, Sweden. Issue 2 (3rd April 2017) - Lundberg, Anna; Strange, Michael
ABSTRACT: The present article elaborates on struggles over the inclusion and exclusion of undocumented children and young people in the Swedish school system. Through conducting an in-depth case study on the issue of access to school in the city of Malmö in Sweden, our analysis demonstrates how the right to education for undocumented migrant children is subject to a process of struggle between divergent discourses on children's human rights. Internal debates at the city level of governance are identified around, for example, whether the police could be denied access to schools or if contradictory messages from various authorities might lead to a legitimacy problem. Other questions are the registration of grades when the children concerned are reluctant to be put into a register due to the risks involved; and if fictitious names could be used on class lists that police officers can request. As the article shows, these local struggles are an expression of tensions between different levels of governance that are also affected by the migration control regime, as regards rights for children who are residing irregularly. In that respect, there is a struggle over the appropriate legalistic discourse – as in, to which level should it make reference. However, actors contesting a restrictive interpretation of the right to education also make substantial use of, what we call here, an 'experiential' discourse – that is, drawing upon the everyday experiences and feelings of those whose rights are in question. Struggles at the local governance level also have relevance for exploring substantial parts of the broader political context in which the human rights of undocumented migrants are (de)contested.